Competing continuities: What role for the presumption of continuity in the claim to continued statehood of small island states? - Michel Rouleau-Dick (Melbourne journal of international law, 2021)
While statehood is a central concept of international law, an unambiguous definition of it has so far remained elusive. The unprecedented situation of small island nations threatened by the rise in sea levels has created a novel angle of approach to statehood by challenging the necessity of a territory and population for a state to exist. Legal scholars have identified several elements of state practice and rely heavily on the existence of a strong presumption of continuity of existing states in international law to support a claim to continued statehood beyond the loss of its physical indicia (ie population, territory). This article delves deeper into the subject by looking at the presumption of continuity and its past, present and possible future uses in international law and state practice. Throughout this exercise, two competing doctrines of continuity are identified and discussed. One defines the presumption of continuity as that which can be described as a type of ratchet effect, preventing the loss of statehood in most limit cases. Alternatively, the sameness doctrine of continuity, rooted in the rich legal scholarship on state continuity, centres on assessing whether a state is the 'same' before and after internal or external changes such as revolutions or territorial changes. The need for this discussion, the relationship between the two doctrines and their respective applications to the context of low-lying island states are then examined.